Computers and language skills : wage premiums in Vietnam. - Liu, Meng Yiu. (2008)
This paper examines the topic of increasing returns to computer and language skills. Reviewing past literature done on both developed and developing nations, as well as using data derived from a survey of higher education graduates in Vietnam, the research draws a conclusion that both language and computer skills result in an estimated wage premium of 29% when these graduates from a developing country like Vietnam enter the workforce.